Kinerja Dewan Pendidikan Dalam Meningkatkan Mutu Pendidikan - Endang Sri Budi Herawati; Suryadi Suryadi; Jumira Warlizasusi; Rusi Rusmiati Aliyyah (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The government formed the Education Board to ensure the implementation of a democratic and quality education policy through community involvement as education stakeholders. By examining the achievement of the objectives of the establishment of the Education Board, this study wanted to see how the Education Board contributed to improving the quality of Education services in Cirebon District. This research was conducted qualitatively in 2019 with the method of data collection through in-depth interviews, questionnaires, and document studies. The results showed that the Board of Education had not yet optimally contributed. The general public does not understand the existence of the Board of Education. Community participation in education that should be optimized through the School Committee has also not been optimally touched. Collaboration with industry has not been established so that the involvement of the Industrial Business World in the development of Education has not been optimal. The absence of rules regarding budget allocations for the implementation of the Education Board activities, resulting in the Education Board unable to work optimally.